A Unified Monitoring Framework for Energy Consumption and Network Traffic - Clouet, Florentin; Delamare, Simon; Gelas, Jean-Patrick; Lefèvre, Laurent; Nussbaum, Lucas; Parisot, Clément; Pouilloux, Laurent; Rossigneux, François (EAI Endorsed Transactions on Energy Web, 2015)
Providing experimenters with deep insight about the effects of their experiments is a central feature of testbeds. In this paper, we describe Kwapi, a framework designed in the context of the Grid’5000 testbed, that unifies measurements for both energy consumption and network traffic. Because all measurements are taken at the infrastructure level (using sensors in power and network equipment), using this framework has no dependencies on the experiments themselves. Initially designed for OpenStack infrastructures, the Kwapi framework allows monitoring and reporting of energy consumption of distributed platforms. In this article, we present the extension of Kwapi to network monitoring, and outline how we overcame several challenges: scaling to a testbed the size of Grid’5000 while still providing high-frequency measurements; providing long-term loss-less storage of measurements; handling operational issues when deploying such a tool on a real infrastructure.